Light and electron microscopic observations on the structure of the porcupine (Hystrix cristata) adrenal gland - Yilmaz, Sadik; Girgin, Aydin (My University, 2005)
The aim of this study was to investigate the structure of the porcupine adrenal gland by light and electron microscopic observations. For this purpose, six adrenals were collected from three adult porcupines (two male and one female). The tissues were processed for both light and electron microscopy. The adrenal gland consisted of capsula (1.2%), zona glomerulosa (6.6%), zona fasciculata (48.5%), zona reticularis (17.9%) and medulla (25.7%). At the cortico-medullar boundary cortical cells were observed, together with chromaffin cells. The epinephrine cells were smaller and more numerous than the norepinephrine cells. Also, the epinephrine granules were moderately electron-dense, while norepinephrine granules were highly electron-dense. Both epinephrine and norepinephrine granules were similar in size and generally formed little rods. The results of the present study are the first report on the structure of the adrenal gland of porcupine.
Keywords: Adrenal gland; Hystrix cristata; Porcupine; Rodentia; Ultrastructure